Jobs for justice(s): Corruption in the Supreme Court of India - ANEY, Madhav S. (Institutional Knowledge at Singapore Management University, 2021)
We investigate whether judicial decisions are affected by career concerns of judges by analyzing two questions: Do judges respond to incentives to pander by ruling in favor of the government in the hope of receiving jobs after retiring from the Supreme Court? Does the government reward judges who rule in its favor with prestigious jobs? We construct a data set of Supreme Court of India cases involving the government for 1999–2014. We find that incentives to pander have a causal effect on judicial decision-making, and they are jointly determined by the importance of the case and whether the judge retires with enough time left in a government’s term to be rewarded with a prestigious job. We also find that authoring favorable judgments increases the likelihood of being appointed to prestigious post–Supreme Court jobs. This suggests the presence of corruption in the form of government influence over judicial decisions.